Examining Factors Affecting Firm Value For F&B Companies - Lia; Kurniawan, Clarissa; Jayakusuma, Josua; Tannia; Zubaedah, Siti Yasmina (Fakultas Ekonomi dan Bisnis Universitas Pekalongan, 2025)
As the F&B industry plays an important role in attaining national food resilience, maintaining sustainably good performance is a heightened concern for all stakeholders. Consequently, F&B companies are heavily scrutinized by investors who commonly use firm value as a business performance indicator. In this study, the authors intend to analyze the influence of liquidity, profitability, and capital structure ratios on firm value in the F&B subsector listed in the Indonesia Stock Exchange from 2014 to 2024. With a sample of 33 firms and 10-year ratios for a total of 363 data points, the research method combines descriptive statistics and multiple regression analysis using Smart PLS 4. The research results show a significant relationship between the profitability variable and firm value. On the contrary, capital structure and liquidity were found not to have any effects on firm value. For practitioners, this research provided evidence on the centrality of profitability not only to attain high firm value but also to portray a positive signal to the public and convince investors. In addition, for investors, this research provides recommendations on several factors to consider when investing capital.